2009 IEEE International Symposium on Information Theory 2009
DOI: 10.1109/isit.2009.5205457
|View full text |Cite
|
Sign up to set email alerts
|

On multiple access random medium access control

Abstract: Abstract-In this paper, we develop a new class of medium access control protocol, which allows each user to transmit at different data rates chosen randomly from an appropriately determined set of rates. By using successive interference cancellation, multiple packets can be received sim ultaneously. In slotted Aloha type Gaussian networks, we show that the achievable total throughput of the proposed protocol is at least a constant fraction of the mac sum rate when the number of transmission rates at each node … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Convexity feature is necessary for designing an optimal distributed algorithm and each node has a global convex utility function [15,34,35]. In [2,21,23,36] there are examples of how utility functions are designed and also it includes determination of contention criterion through reverse engineering from existing protocols and from desirable performance points (according to throughput and fairness) and through forward engineering in a heuristic manner as the following.…”
Section: Carrier Sense Multiple Access Tuning Parameters Based On Gam...mentioning
confidence: 99%
See 1 more Smart Citation
“…Convexity feature is necessary for designing an optimal distributed algorithm and each node has a global convex utility function [15,34,35]. In [2,21,23,36] there are examples of how utility functions are designed and also it includes determination of contention criterion through reverse engineering from existing protocols and from desirable performance points (according to throughput and fairness) and through forward engineering in a heuristic manner as the following.…”
Section: Carrier Sense Multiple Access Tuning Parameters Based On Gam...mentioning
confidence: 99%
“…(5) (6) In [22] service differentiation has been provided through defining different utility functions according to traffic classes with different weights as a non cooperative game. In most researches including [2,21,23,36] only cellular wireless local networks have been taken into account in which each node hears transmissions of other nodes. Also it is assumed that all nodes are saturated, channel is free from error and packet drop occurs only in a result of collision.…”
Section: Carrier Sense Multiple Access Tuning Parameters Based On Gam...mentioning
confidence: 99%
“…Amongst related work, several studies have shown that interference cancellation techniques bring out benefits in the context of random multiple access. As an example, in [10] the authors study successive interference cancellations applied to each time slot. In network coding area, the joint use of classical network coding (i.e.…”
Section: Introduction and Related Workmentioning
confidence: 99%
“…Let each corner point of R be an n-tuple whose elements are among the numbers R 1 , · · · , R L−1 and R L . With no cooperation among the users, the authors in [22] propose that each user selects a codebook of rate R l with probability p l ∈ (0, 1) for 1 ≤ l ≤ L. Assuming the receiver is aware of the rate selection of all users, the average sum rate of the network isR = l 1 ,··· ,ln∈{1,··· ,L} p l 1 · · · p ln (R l 1 + · · · + R ln )1 (R l 1 ,··· ,R ln )∈R where 1 (R l 1 ,··· ,R ln )∈R is 1 if (R l 1 , · · · , R ln ) ∈ R and 0 otherwise. Finally, the numbers p 1 , · · · , p L−1 and p L are derived to maximizeR.…”
mentioning
confidence: 99%